PERBEDAAN STABILITAS WARNA BAHAN BASIS GIGI TIRUAN RESIN AKRILIK DENGAN RESIN NILON TERMOPLASTIS TERHADAP PENYERAPAN CAIRAN - Naini, Amiyatun (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Base materials of removable partial denture are usually from acrylic and thermoplastic nylon resin. Both of materials have advantages and disadvantages. Acrylic resin properties have good esthetic, the color like gum, cheap, and easy to repair it. The disadvantage is easy to porous. Thermoplastic nylon resin is flexible material, not use retention wire, thinner, more translucent, has goo esthetic, and difficult to be broken. Disadvantages of this resin are easy to be shrinkage, to absorp water and dimensional changes. One of effort to clean denture is by soaking in some liquid for 6 â 8 hours. Denture always contacts with saliva or drinking water. Aim of this study is to know the different of denture base color stability of acrylic and thermoplastic nylon resin toward liquid absorption. Samples were acrylic and thermoplastic nylon resin in and soaked in aquadest for 7 days. The control is sampels before soaked in aquadest. Color stability was tested densitometer. The result showed there was significant different color stability between acrylic and thermoplastic nylon resin that before and after soaking in aquadest for 7 days. The conclussion is thermoplastic nylon resin absorpt liquid more than acrilyc resin and it made color changing.